A candidate fusion engineering material, WC-FeCr - Humphry-Baker,S; Harrison,R; Greaves,G; Knowles,A; Smith,G; Donnelly,S; Lee,W (Scripta Materialia, 2018)
A new candidate fusion engineering material, WC-FeCr, has been irradiated with He ions at 25 and 500°C. Ions were injected at 6keV to a dose of ~15dpa and 50at. % He, simulating direct helium injection from the plasma. The microstructural evolution was continuously characterised in situ using transmission electron microscopy. In the FeCr phase, a coarse array of 3–6nm bubbles formed. In the WC, bubbles were less prominent and smaller (~2nm). Spherical-cap bubbles formed at hetero-phase interfaces of tertiary precipitates, indicating that enhanced processing routes to minimise precipitation could further improve irradiation tolerance.